The 1991-1996 NATMAP Slave Province Project: Introduction - Bleeker, Wouter; Davis, W J (Canadian Journal of Earth Sciences, 1999)
The 11 papers contributed to this issue on the geology of the Slave Province are summarized, and where appropriate, links between data from the various contributions are emphasized. In the discussion, we provide a synthesis of the present knowledge base on pre-Yellowknife Supergroup basement rocks throughout the Slave Province. All available age data on Mesoarchean and Paleoarchean basement rocks are compiled and, in a first attempt to seek regional correlations, 10 "events" of crustal growth and (or) reworking are recognized, spanning well over 1 billion years of Earth's history. The spatial distributions of these events across the craton are discussed. Finally, we pose a series of important questions that remain and that may help guide future research.